Computational study of photoexcited dynamics in bichromophoric cross-shaped oligofluorene - Ondarse Alvarez, Dianelys (2014)
The non-adiabatic excited state molecular dynamics (NA-ESMD) approach is applied to investigate photoexcited dynamics and relaxation pathways in a spiro-linked conjugated polyfluorene at room (T = 300 K) and low (T = 10 K) temperatures. This dimeric aggregate consists of two perpendicularly oriented weakly interacting α-polyfluorene oligomers. The negligible coupling between the monomer chains results in an initial absorption band composed of equal contributions of the two lowest excited electronic states, each localized on one of the two chains. After photoexcitation, an efficient ultrafast localization of the entire electronic population to the lowest excited state is observed on the time scale of about 100 fs. Both internal conversion between excited electronic states and vibronic energy relaxation on a single electronic state contribute to this process. Thus, photoexcited dynamics of the polyfluorene dimer follows two distinct pathways with substantial temperature dependence on their efficiency. One relaxation channel involves resonance electronic energy transfer between the monomer chains, whereas the second pathway concerns the relaxation of the electronic energy on the same chain that has been initially excited due to electron-phonon coupling. Despite the slower vibrational relaxation, a more efficient ultrafast electronic relaxation is observed at low temperature. Our numerical simulations analyze the effects of molecular geometry distortion during the electronic energy redistribution and suggest spectroscopic signatures reflecting complex electron-vibrational dynamics.